Asia-Pacific Journal of Molecular Biology and Biotechnology (Universiti Malaya, 2005)
The Journal aims to promote research in all relevant areas of molecular & cellular biology and biotechnology in the Asia Pacific region through publication of research articles, both basic and applied.